First molecular characterization of Galba neotropica in Uruguay (FAVE Sección Ciencias Veterinarias, 2016)
Until recently, it was believed that only two lymnaeid species (i.e. Galba viatrix and Pseudosuccinea columella) occurred in Uruguay. However, based on a molecular approach, an additional species Galba cubensis, was recently discovered. The aim of this study was to molecularly characterize different lymnaeid populations from the northern region of Uruguay. The lymnaeids collections were carried out in two farms of the departments of Paysandú and Tacuarembó. The collected lymnaeids were divided in two fractions, one fraction was used for conchological analyses and detection of trematode larval stages, while the other fraction was used for molecular studies. Three PCRs targeting the 16S, ITS-2 and COI DNA regions were performed and the amplicons obtained were direct sequenced. The sequences were used for homology search and construction of phylogenetic trees by the maximum-likelihood method. The sequencing results revealed that both isolates corresponded to Galba neotropica. The phylogenetic analyses placed our isolates among the G. neotropica monophyletic group, closely related to other isolates of this species found in several South American countries. To our knowledge, this is the first record of G. neotropica in Uruguay and the confirmation as competent intermediate host of Fasciola hepatica. Further studies are needed to define the distribution and the role of each lymnaeid species in the transmission of F. hepatica in Uruguay. RESUMEN. Primera caracterización molecular de Galba neotropica en Uruguay. Tradicionalmente se indicaba que existían dos especies de limneidos en Uruguay: Galba viatrix y Pseudosuccinea columella. Sin embargo, en los últimos años se identificó por medio de técnicas moleculares una tercera especie, Galba cubensis. El objetivo de los autores fue muestrear e identificar por medios moleculares poblaciones de limneidos del norte del país. Las colectas fueron realizadas en establecimientos rurales de los departamentos de Tacuarembó y Paysandú. Los caracoles colectados fueron divididos en dos fracciones, una de ellas fue destinada para el estudio morfológico de las conchillas y búsqueda de larvas de trematodos. La otra fracción se usó para la caracterización molecular. Tres genes fueron amplificados (ITS2, COI y 16S) utilizando protocolos de PCRs previamente descriptos. Las secuencias obtenidas se utilizaron para estudios de homología y construcción de árboles filogenéticos por medio del método de máxima verosimilitud. Por medio de la secuenciación se pudo confirmar que los dos aislamientos corresponden a Galba neotropica. Los estudios filogenéticos colocan ambos aislamientos dentro del grupo monofilético de G. neotropica junto a otros encontrados en distintas regiones de Sudamérica. Hasta lo que sabemos, el presente, es el primer registro de G. neotropica en Uruguay, además de comprobarse su capacidad para actuar como hospedero intermediario de Fasciola hepatica en condiciones de campo.  Se sugieren futuros estudios para determinar la distribución y el rol de cada especie de limneido en la transmisión de F. hepatica.